Flowering phenology of species with similar flower colours in species-rich communities - Camargo, Maria Gabriela Gutierrez; Arista, Montserrat; Lunau, Klaus; Ortiz, Pedro Luis; Stradic, Soizig Le; Rocha, Nathália Miranda Walter Bretas; Morellato, Leonor Patrícia Cerdeira (Flora. Morphologie, Geobotanik, Oekophysiologie, 2023)
•We tested hypothetical scenarios for the interaction between bee-flower colours and flowering phenology.•Species-rich taxa have similarly coloured flowers in megadiverse campo rupestre and Mediterranean vegetation•Divergence in flowering phenology may decrease interspecific competition•A standardised floral signal may improve pollinator attraction (i.e., induce facilitation)•Patterns of flowering phenology and flower colour suggest that flower-signal standardisation benefits species-rich vegetation Within a community, co-occurring plant species are expected to diverge in floral display or flowering phenology to decrease interspecific competition and thus increase intraspecific pollination. However, co-occurring species can also benefit from floral signal standardisation (similar colour signals among flowers of different species) because it facilitates pollinator attraction. Considering the interaction of flower colour display and flowering phenology, we investigated the visual similarity of rewarding flowers among species from highly diverse tropical and temperate vegetation types. For six groups of co-occurring, closely related bee-pollinated species with similar floral displays from Brazilian campo rupestre (51 species) and Spanish Mediterranean vegetation (30 species), we first investigated whether flower colours can be discriminated by bees based on colour locus distance in the bee vision hexagon. We then tested whether flowering phenology overlapped or was segregated. We found that within both vegetation regions, flower colour was generally not distinguishable within groups by bees. The small perceptual distance of colour loci in the bee visual space did not enable discrimination. The flowering periods of the Mediterranean species overlapped, while the Brazilian campo rupestre species tended to have segregated phenologies. Mediterranean species may benefit from the increased standardisation of signals displayed during the short flowering season, while the sequential flowering phenology of campo rupestre species may decrease interspecific competition and help maintain a recognizable signal for bees over time, favouring flower constancy. We concluded that the standardisation of the floral colour signal within these two species-rich plant communities is advantageous for most of the species studied, despite having different flowering phenologies.